2019
DOI: 10.18535/jmscr/v7i4.117
|View full text |Cite
|
Sign up to set email alerts
|

A study on Socio- Demographic Profile, Prevalence of Hypertension and its association with other factor in school going Adolescents of Gorakhpur City

Abstract: Background: Hypertension is a chronic condition of concern due to its role in causation of coronary heart diseases, stroke and other vascular complications. Assessment of prevalence of hypertension in school going adolescents is one of the best way to assess the prevalence of hypertention among adolescents. So the Objectives of the study is to determine the prevalence of hypertension among the school going adolescents of Gorakhpur city. Method: A cross-sectional study was carried out from September 2013 to Aug… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 8 publications
0
1
0
Order By: Relevance
“…According to Singh et al the prevalence of hypertension has increasing trend with increasing age. 11 Hasan et al conducted a study on prevalence of hypertension in Haridwar and found that prevalence of hypertension increased with age. 12 34.6% participants had a family history of hypertension.…”
Section: Discussionmentioning
confidence: 99%
“…According to Singh et al the prevalence of hypertension has increasing trend with increasing age. 11 Hasan et al conducted a study on prevalence of hypertension in Haridwar and found that prevalence of hypertension increased with age. 12 34.6% participants had a family history of hypertension.…”
Section: Discussionmentioning
confidence: 99%